Efek Pemberian Ekstrak Etanol Daun Jarak Merah (Jatropha gossypiifolia L.) terhadap Kadar Glukosa Darah Puasa, Kadar Insulin Serum dan HOMAIR pada Model Tikus DM Tipe 2 - Nugroho Wibisono; Achmad Basori; Suhartati (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2022)
Abstract. Jatropha gossypiifolia L. is a medicinal plant from theEuphorbiaceae family. Jatropha gossypiifolia L. leaves have somemedicinal properties, but their effect on antidiabetics mechanisms isstill unclear. Jatropha gossypiifolia leaves have some activecompounds such as alkaloid, flavonoid, phenol, saponins, tannins,steroid, terpenoid, and triterpenoid. The presentstudy was designedto analyze effect of Jatropha gossypiifolia leaves extract activecompounds on fasting blood glucose levels, serum insulin levels andHOMA-IR. The design of thisresearch istrue experimental with posttest only control group design with independent variables includinga high-fat diet, streptozotocin injections, Jatropha gossypiifolia L.leaves extract in doses of 60, 120, dan 240 mg/kg and dependentvariables including fasting blood glucose levels, serum insulin levels,and HOMA-IR. Based on this study, there were a significantlydifferent between fasting blood glucose levels and HOMA-IR controlgroups than the extract groups. It can be concluded that Jatrophagossypiifolia L. leaves extract has effect on fasting blood glucoselevels, serum insulin levels and HOMA-IR on DM type 2 rat models.